Urgensi Manajemen Keamanan dan Pengendalian Sistem Informasi bagi UMKM di Indonesia - Mahendra Adhi Nugroho; Agatha Yerika Septininditya; R. Andro Zylio Nugraha (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In today's digital era, Micro, Small, and Medium Enterprises (MSMEs) are one of the important components in the national and global economy. In the context of MSMEs in Indonesia, managing and controlling information system security is a very important thing to pay attention to. This article discusses the urgency of steps that need to be taken to support the growth of MSMEs in Indonesia. The method used in this research is descriptive qualitative method. The approach used is library research. Based on the results of the literature study, it was found that the management and control of information systems really need to be applied to MSMEs in Indonesia. This is because threats to information systems and technology in MSMEs are unavoidable conditions. Generally, MSMEs already know this, but they have only taken the most basic information system management and control actions, and there are still many MSMEs that have not taken information system management and control actions.